Stakeholder Participation in Primary Care System Change: A Case Study Examination of the Introduction of the First Nurse Practitioner-Led Clinic in Ontario - O'Rourke, Tammy (Université d'Ottawa / University of Ottawa, 2013)
Purpose: To examine stakeholder participation in the primary care system change process that led to the introduction of the first Nurse Practitioner-Led Clinic in Ontario. Design: Qualitative case study guided by the principles of stakeholder and system change theory. Setting: Northern Community in Ontario, Canada. Participants: Purposeful sample of healthcare providers, healthcare managers and health policy stakeholders. Procedures: This case study was bound by place (Sudbury), time (January 2006–January 2008), activity (stakeholder participation), and process (introduction of an innovation, the first Nurse Practitioner-Led Clinic in Ontario, during a primary care system change). Semi-structured individual interviews were conducted with participants who represented the clinic, the local community, and the province. Public documents, such as newspaper articles published during the 2 year time boundary for this case and professional healthcare organization publications, were also examined. Interviews were analyzed using qualitative content analysis and public documents were reviewed for key messages to complement the interview findings. Field notes written during data collection and analysis were used to provide additional depth, contribute insights to the data, and ascribe meaning to the results. Main Findings: Sixteen interviews were conducted with key stakeholders. Twenty public documents which yielded the most specific information relevant to the case study time boundaries and activities were selected and reviewed. Six main themes are reported: felt need, two visions for change (one for a Nurse Practitioner-Led Clinic and one for Family Health Teams [FHTs]), vision processes related to ensuring the visions became or continued to be a reality in Ontario’s healthcare system (shaping, sharing, and protecting the vision), stakeholder activities, and sustaining and spreading the vision. Conclusions: In this case, stakeholder participation influenced policy decisions and was a key contributor to the primary care system change process to introduce the first Nurse Practitioner-Led Clinic in Ontario. Stakeholders are motivated by various needs to engage in activities to introduce an innovation in primary care. One of the most common needs felt by both those who supported the introduction of the first Nurse Practitioner-Led Clinic and those who were opposed to it was the need for improved patient access to primary care.
Keywords: Stakeholder; Vision; Nurse Practitioner; Change